Layer-by-Layer Films Based on Carbon Nanotubes and Polyaniline for Detecting 2-Chlorophenol - Silva, Juliana S.; Barros, Anerise de [UNESP]; Constantino, Carlos J. L. [UNESP]; Simoes, Fabio R.; Ferreira, Marystela (Amer Scientific Publishers, 2014)
Electrochemical sensors made with layer-by-layer (LbL) films of functionalized multi-walled carbon nanotubes (MWCNT5-COO-) and polyaniline (PAni) deposited onto ITO substrates were used to detect 2-chlorophenol. Concentrations down to ppm level could be detected with square wave voltammetry (SWV), owing to synergistic effects between PAni and nanotubes, whose molecular-level interactions in the LbL films were inferred using FTIR and Raman spectroscopy. Significantly, the Raman spectra of MWCNTs-COO-/PAni LbL films indicated that the conducting properties of PAni were preserved upon adsorption on the ITO substrates, with homogeneous nanocomposites being formed according to Scanning Electron Microscopy (SEM) images.
Keywords: Layer-by-Layer Films; PAni; Multi Walled Carbon Nanotubes; 2-Chrophenol Sensors; Electrochemical Sensors